2002
DOI: 10.1002/1521-3757(20020402)114:7<1253::aid-ange1253>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Helical Sense Bias Induced by Point Chirality in Cage Compounds

Abstract: Chiralität für den Propeller: Bei der Herstellung von chiralen Käfigen mit Propeller‐artigem Aufbau und Pseudo‐C3‐Symmetrie (siehe Bild; R=H, Cl) lässt sich durch Kontrolle der topologischen Asymmetrie ein ausgezeichneter Chiralitätstransfer erzielen. Zwei tripodale Einheiten werden durch drei P=N‐Bindungen verknüpft, ein „Tripod‐Tripod‐Kupplungsprozess“, der von einer bemerkenswerten dreifachen Stickstoffabspaltung begleitet ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These porous cages have attracted much attention recently, with applications in sensing, 17 gas storage, 18 catalysis, 19 and chiral induction. 20 Since the cryptand cavity offers a confined space wherein the weak noncovalent interactions can be amplified, it can provide a favorable platform to study and analyze halogen and other weak noncovalent interactions with even the weakest halogen bond donors. For this purpose, we envisioned a rational design of a cryptand incorporating multiple electron-rich pyrazole aromatic rings where both halogen and hydrogen bonding interactions can be utilized (Scheme 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…These porous cages have attracted much attention recently, with applications in sensing, 17 gas storage, 18 catalysis, 19 and chiral induction. 20 Since the cryptand cavity offers a confined space wherein the weak noncovalent interactions can be amplified, it can provide a favorable platform to study and analyze halogen and other weak noncovalent interactions with even the weakest halogen bond donors. For this purpose, we envisioned a rational design of a cryptand incorporating multiple electron-rich pyrazole aromatic rings where both halogen and hydrogen bonding interactions can be utilized (Scheme 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have shown that the sense of twist ( P / M ) of the helical asymmetry of cages 2 , bearing a single chiral carbon atom on one of their arms, is totally controlled by the absolute configuration of the stereogenic center (Figure ) . This kind of control represents one of the scarce examples of center-to-propeller chirality transfer reported at the molecular level in discrete organic molecules until now …”
mentioning
confidence: 91%
“…Helical assemblies have long been the best recognized examples in this field . In addition to helical structures constituted by one or more covalent organic strands, the “molecular propeller” arrangement which possesses two or more subunits as “blades” radiating from an axis of rotation (the propeller axis) represents an interesting topic . Achiral molecules with C 3 symmetry have been employed to construct both organic 6 and inorganic chiral structures.…”
Section: Introductionmentioning
confidence: 99%